Juridical Analysis of Maritime Law in the Context of Responsive and Accommodative Legal Reform - Hapsari , Tania Resti (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Indonesia’s vast maritime territory faces persistent challenges, including illegal fishing, territorial violations, and marine environmental degradation, highlighting the urgency of responsive and accommodative maritime legal reform. This study aims to analyze Indonesia’s maritime law through a juridical lens, integrating sociological perspectives to address socio-technological changes. Grounded in Responsive Law Theory, Accommodative Law Theory, and Maritime Sovereignty Theory, the research employs a normative legal approach and literature study to examine statutory provisions, international conventions, and relevant scholarly works. Findings reveal a significant gap between regulatory norms and practical enforcement, limited community participation, and inadequate integration of technology in maritime governance. The study underscores the need for legal frameworks that are adaptive, participatory, and aligned with international standards while safeguarding national sovereignty. Recommendations include institutional strengthening, technology integration, and stakeholder engagement. This research contributes an integrated model for maritime legal reform that harmonizes sovereignty, justice, and sustainability.